Effectiveness of collagen extracted from the skin of Nile tilapia fish (Oreochromis niloticus) to accelerate wound healing in vivo: a narrative review - Dazrulhafizi, Nurul Nur Fazzana; Ismail, Elysha Nur; Ishak, Reezal (Universiti Putra Malaysia Press, 2023)
Developing wound dressings with good properties to accelerate wound healing has always been challenging. Mammal collagen is well known as the desired choice among naturally pro-duced dressings despite experiencing major drawbacks. Therefore, researchers have explored the by products of Oreochromis niloticus fish or red Nile tilapia, such as the scales and skin as alternative source of collagen. This narrative review analyzes the effectiveness of collagen extracted from Oreochromis niloticus skin and its beneficial properties to accelerate wound healing in vivo. Recent studies were compiled to provide a compact review on the effective-ness of the collagen in hastening wound healing process. Faster wound closure with upregulation of multiple growth factors, and high hydroxyproline content are some of the findings. The collagen extract could also promote the formation of epidermal layers, fibroblasts proliferation, and dermal reconstitution. Thus, Oreochromis niloticus skin collagen extract has the potential to be developed as an effective wound dressing.